Analisis Pelaku UMKM Produk Ketempling terhadap Praktik Persaingan Tidak Sehat: Studi Kualitatif di Kota Kuningan - Anisa Fatmasari; Anggi Susanti; Siti Khodijah (Letterlijk, 2025)
This study analyzes the responses of Micro, Small, and Medium Enterprises (MSMEs) in dealing with unfair business competition in the traditional food sector, particularly ketempling products in Kuningan Regency. The research employs a qualitative approach using interviews with two ketempling MSME actors as informants. The findings indicate that MSMEs experience competitive pressure, especially in terms of price competition and product similarity. Nevertheless, the business actors choose not to engage in unfair practices such as extreme price cutting or product imitation. Instead, they emphasize product quality, the use of high-quality raw materials, and improved consumer services as their main survival strategies. In addition, the utilization of social media and product diversification plays an important role in adapting to increasingly competitive market conditions, particularly in the post–COVID-19 period. This study concludes that business strategies oriented toward quality, innovation, and business ethics represent a sustainable approach for MSMEs to withstand unfair competition and build a positive business image among consumers.